Gaya Hidup Cashless dan Pemanfaatan Dompet Digital dalam Membentuk Perilaku Konsumtif Mahasiswa Generasi Z: Peran Self-Control dan Nilai-Nilai Islam - Sri Kasnelly; Ahmad Luthfi; Abdul Jalil; M. Syaikhul Arif; Revalina Juventini LA (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Advances in digital payment technology have reshaped how Generation Z students consume, largely through their growing embrace of a cashless lifestyle and digital wallets. This study set out to determine whether a cashless lifestyle and the intensity of digital wallet use shape consumptive behavior, examining self-control as a mediating mechanism and Islamic values as a moderating factor. Using a purposive sample of 80 students from Universitas Islam An-Nadwah Kuala Tungkal, quantitative survey data were gathered and processed through SEM-PLS. Findings indicate that both a cashless lifestyle and digital wallet usage intensity raise consumptive behavior, whereas self-control and Islamic values lower it. Islamic values were found to moderate only the self-control-to-consumptive-behavior pathway, while self-control failed to mediate the pathways linking cashless lifestyle or digital wallet usage to consumptive behavior. Taken together, the results underscore that cultivating self-control and instilling Islamic values are key to fostering wiser consumption habits among students.